Research on low density polyethylene (LDPE), recycled by advanced thermal analysis (DSC, TG) - Siwczyk, Bartosz; Schlafka, Paweł; Sąsiadek, Michał; Woźniak, Waldemar (Zielona Góra: Uniwersytet Zielonogórski)
This article presents the issue of recycling and maintaining the processing properties of materials made of plastics. For this purpose, samples from recycled, low-density, polyethylene were tested. The impact of the use of dyes and surface printing on the lifecycles of material and its quality was examined. For this purpose, an analysis was carried out using differential scanning calorimetry and thermos-gravimetry. It was found that the use of dyes may affect the quality of the material and increase the disposal costs of pre-used materials.
Keywords: DSC; TG; LDPE; plastics recycling; thermal analysis